Reconstruction of Richard Matheson’s Button, button - Haqiqi Ranu Antariksa Saputra; Thohiriyah (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This study analyzes how the story reveals hidden systems of control. It shows how modern economic system trick people into thinking they're making free choices, when they're actually being manipulated. The method in this research is using close reading approach as well as the triadic form of construction-deconstruction-reconstruction, it work by establishing themes and binary oppositions in a story first, then deconstruct it by flipping the binary oppositions, and then reconstruct it by creating a new interpretation of the story based from deconstructed binary oppositions and themes. The triadic analysis uncovers contradictions, where Pandora's myth attributes evil to divine forces, Matheson's story attributes it to a systems that tempt and make Norma, the main character, into thinking that she got a free will over her choice. This research concludes that Norma thinks she's making a real choice, just like Pandora gave in to curiosity. But the shocking ending shows she was never really in control, the system had already decided her fate. This exposes how those in power fake 'freedom' to keep people under their thumb.